Correction: Corrigendum: A simple and versatile design concept for fluorophore derivatives with intramolecular photostabilization - Jasper H. M. van der Velde (Nature Portfolio, 2017)
Nature Communications 7 Article number: 10144 (2016) Published: 11 January 2016; Updated: 04 August 2017 The original version of this Article contained an error in the spelling of the author Giorgos Gouridis which was incorrectly given as Giorgos Guoridis. This has now been corrected in both the PDFand HTML versions of the Article.